2013
DOI: 10.5607/en.2013.22.4.244
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives of Dyrk1A Role in Neurogenesis and Neuropathologic Features of Down Syndrome

Abstract: Down syndrome (DS) is one of the most common genetic disorders accompanying with mental retardation, cognitive impairment, and deficits in learning and memory. The brains with DS also display many neuropathological features including alteration in neurogenesis and synaptogenesis and early onset of Alzheimer's disease (AD)-like symptoms. Triplication of all or a part of human chromosome 21, especially the 21q22.1~21q22.3 region called 'Down syndrome critical region (DSCR)', has been considered as the main cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 38 publications
(48 reference statements)
0
49
0
5
Order By: Relevance
“…Several recent reviews have discussed in detail the numerous targets of Dyrk1a , and have suggested how molecular mechanisms altered by excessive Dyrk1a could affect cognitive and behavioral processes (Wegiel et al. ; Park and Chung ; Duchon and Herault ; Antonarakis ). In addition, several reports have described potential Dyrk1a inhibitors and their possible use for correcting DS‐related deficits (de la Torre and Dierssen ; Becker et al.…”
Section: The Role Of Ds Mouse Models In Finding Therapiesmentioning
confidence: 99%
“…Several recent reviews have discussed in detail the numerous targets of Dyrk1a , and have suggested how molecular mechanisms altered by excessive Dyrk1a could affect cognitive and behavioral processes (Wegiel et al. ; Park and Chung ; Duchon and Herault ; Antonarakis ). In addition, several reports have described potential Dyrk1a inhibitors and their possible use for correcting DS‐related deficits (de la Torre and Dierssen ; Becker et al.…”
Section: The Role Of Ds Mouse Models In Finding Therapiesmentioning
confidence: 99%
“…When present in three copies, DYRK1A is one of two genes thought to be primarily responsible for neurocognitive deficits associated with Down syndrome. 9, 10 Previously, disruption due to translocation or deletion of DYRK1A was reported in four individuals with intellectual disability (ID), primary microcephaly and overlapping facial dysmorphisms (Supplementary Figure 1) pointing towards a possible emerging syndrome. 1113 Four individuals with DYRK1A variants have recently been concisely reported.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Out of the autosomal genes known to have a role in severe ID, the dual-specificity tyrosine-phosphorylation-regulated kinase (DYRK1A) gene (OMIM 600855) has been one of the most extensively studied. [8][9][10][11] Interest in DYRK1A originated because of its genomic localization within the Down syndrome critical region (DSCR) on chromosome 21q22, a chromosomal region that is presumed to be largely responsible for the neuropathologic abnormalities observed in Down syndrome. 12 DYRK1A exhibits an extraordinarily high degree of protein sequence conservation in animals across all vertebrates, 13 and animal models have been instrumental in determining the functions of the encoded proline-directed serine/threonine kinase.…”
Section: Introductionmentioning
confidence: 99%